Prenatal Alcohol Exposure Results in Sex-Specific Alterations in Circular RNA Expression in the Developing Mouse Brain - Paudel, Praveen; Pierotti, Caroline; Lozano, Evelyn; Amoah, Stephen K.; Gardiner, Amy S.; Caldwell, Kevin K.; Allan, Andrea M.; Mellios, Nikolaos (Frontiers in Neuroscience, 2020)
Fetal Alcohol Spectrum Disorders (FASD) are heterogeneous disorders associated with alcohol exposure to the developing fetus that are characterized by a range of adverse neurodevelopmental deficits. Despite the numerous genomics and genetic studies on FASD models, the comprehensive molecular understanding of the mechanisms that underlie FASD-related neurodevelopmental deficits remains elusive. Circular RNAs (circRNAs) are a subtype of long non-coding RNAs that are derived from back-splicing and covalent joining of exons and/or introns of protein-coding genes. Recent studies have shown that circRNAs are highly enriched in the brain, where they are developmentally regulated. However, the role of the majority of brain-enriched circRNAs in normal and pathological brain development and function has not been explored yet. Here we carried out the first systematic profiling of circRNA expression in response to prenatal alcohol exposure (PAE) in male and female embryonic day 18 (E18) whole brains. We observed that the changes in circRNA expression in response to PAE were notably sex-specific and that PAE tended to erase most of the sex-specificity in circRNA expression present in control (saccharin-treated) mice. On the other hand, RNA sequencing (RNA-seq) in the same samples showed that changes in protein-coding gene expression were not predominantly sex-specific. Using circRNA quantitative real-time PCR (qRT-PCR), we validated that circSatb2, which is generated from the special AT-rich sequence-binding protein 2 (Satb2) gene, is significantly upregulated in the brain of E18 male PAE mice. We also show that circPtchd2, a circRNA synthesized from dispatched RND transporter family member 3 (Disp3, also known as Ptchd2), exhibits significantly higher expression in E18 control but not PAE female mouse brain relative to males. Taken together, our results demonstrate that PAE differentially alters circRNA expression in the developing brain in a sex-specific manner.